COMPATIBILITY OF NATIVE POTENTIAL BIOAGENTS WITH DIFFERENT FUNGICIDES AGAINST COLLETOTRICHUM GLOEOSPORIOIDES PENZ. CAUSING MANGO ANTHRACNOSE - BASHA, S. THAHIR; J. SUVARNA; T. M. HEMALATHA; REDDY, N. P. ESWARA (The Bioscan, 2009)
Managing the anthracnose through chemicals alone is not satisfactory in view of the development of resistance, environmental concerns and cost benefit ratio. Some reports are available regarding the resistance of C. gloeosporioides to fungicides in mango and as well as in other crops. Keeping this in view, ninety six native potential antagonists were isolated from phylloplane and leaf endophytes during the roving survey conducted in different regions of Andhra Pradesh. Of the 96 antagonists screened by dual culture technique, four fungal and six bacterial antagonists identified as fungicidal tolerant potential bioagents. Further these antagonists were evaluated for their compatibility with commonly used four systemic fungicides viz., carbendazim (50 ppm), thiophanate-methyl (50 ppm), propioconazole (25 ppm), hexaconazole (25 ppm) and two non-systemic fungicides viz., mancozeb (1000 ppm) and copper oxychloride (1000 ppm) to manage the disease through an integrated approach by combining bioagents and economic use of chemicals